Displaced lives and social networks: Lived experiences of climate migrants in Bangladesh - Wafa Alam; Sabina Faiz Rashid; Yasmin Ara; Muhammad Riaz Hossain; Tasmiha Amin Oishy; Nusrat Jahan Nizum (Journal of Community Systems for Health, 2026)
Introduction: Climate-induced migration poses significant challenges to vulnerable populations, particularly in low-income developing countries like Bangladesh, where climate change has already displaced over 7.1 million people and this number is expected to reach 13.3 million by 2050. This study explores the lived experiences of climate-induced migrants in urban informal settlements in Bangladesh, focusing on how displacement, structural oppression, and social networks shape their adaptation and wellbeing. Methods: Using a qualitative, community-based participatory research approach under the ARISE project, data were collected through case studies in three urban sites: Dhaka, Khulna, and Satkhira, between 2022 and 2023, comprising nine individual case studies. Results: Migration is often a last resort following recurrent climate disasters such as cyclones, floods, and river erosion that destroy homes, land, and livelihoods. Upon relocation, migrants face new challenges including inadequate housing, scarce job opportunities, food insecurity, and limited access to healthcare. Social networks play a crucial role in navigating these challenges by facilitating access to work, housing, and informal healthcare. However, migrants remain trapped in cycles of poverty and marginalization, with both new and long-term residents vulnerable to eviction and economic precarity. Conclusions: The study concludes that climate-induced migration in Bangladesh is not by choice and is shaped by intersecting social and structural inequalities. Policy interventions must recognize the agency of migrants while addressing systemic barriers to health, housing, and employment, ensuring the rights and wellbeing of climate-affected populations are protected.